Клініко-діагностичні критерії за гострої ниркової недостатності у собак - Cуслова, Наталія Іванівна; Suslova, Natalіya; Шульженко, Наталія Миколаївна; Shulzhenko, Nataliya; Shulzhenko, N. M.; Семьонов, Олександр Володимирович; Semonov, Oleksandr; Semyonov, O. V.; Шкваря, Микола Миколайович; Shkvarya, Mikola; Shkvaria, M. M.; Панасенко, Євген Анатолійович; et al. (Дніпровський ДАЕУ, 2018)
Наведено результати дослідження собак з ознаками гострої ниркової недостатності. Встановлено загальні принципи діагностики, які ґрунтуються за даної патології на клінічних, лабораторних та додаткових методах дослідження. За даними анамнезу та результатами клінічного дослідження у собак виявлено тривале недостатнє кровопостачання нирок за гіпотензії внаслідок зневоднення, кровотечі, анестезії, операції або травми. У тварин виявляли олігурію або анурію, порушення функцій центральної нервової, серцево-судинної, дихальної і травної систем. Встановлено збільшення сечовини та креатиніну за біохімічного дослідження крові собак, відповідно до 18,7±0,88 ммоль/л та 259,6±10,22 мкмоль/л, збільшення відносної густини сечі вище 1,040 г/мл. За даними доплерографії судин нирок виявили ішемію паренхіми нирки, яка обумовлена порушенням притоку артеріальної крові. Лікування було направлене на відновлення гомеостазу та усунення причини. Для цього застосовувалась інфузійна терапія, корекція електролітного дисбалансу, етіотропне лікування, за необхідності – діуретики для відновлення діурезу. Diagnosis of kidney disease, despite the high level of nephrology development, is a significant problem in veterinary medicine. Therefore, a qualified study of the urinary system should be based on the integrated application of traditional and modern instrumental research methods. The purpose of this work is to characterize the clinical status of dogs with renal insufficiency and find out the informative value of intravital diagnosis of renal insufficiency with the help of ultrasound and dopplerography. The research was conducted during 2016-2017 in the scientific and educational clinical diagnostic center of the faculty of veterinary medicine of the Dnipro State Agrarian and Economic University of Dnipro city (DSAEU), Ukraine. 10 dogs with signs of acute renal insufficiency were selected for this study. The main diagnostic stages in acute renal insufficiency in dogs included anamnesis, clinical examination, blood and urine analysis, additional researching methods (ultrasound and dopplerography of kidneys). Prolonged insufficient blood supply to the kidneys with the hypotension due to dehydration, bleeding, anesthesia, surgery or trauma were observed in dogs according to the disease history and results of a clinical study during the acute kidney insufficiency. In the initial stage of acute renal insufficiency, a decrease of diuresis was observed, the amount of urine sharply decreased to anuria, the function of the central nervous, cardiovascular (hypertension), respiratory and digestive systems was disrupted. As a result of azotemia, there appeared vomiting, apathy and drowsiness. Dogs showed an increase in the relative density of urine above 1.040 g/ml, due to dehydration. There were no signs of inflammation in the urine sediment. Biochemical blood indices of dogs with acute renal insufficiency have been showing a gradual and rapid increase of urea and creatinine, respectively, to 18.7 ± 0.88 mmol/L and 259.6 ± 10.22 μmol/L. According to the results of ultrasound examination of kidneys, there was no renal origin of acute renal insufficiency. Doppler ultrasonography of the kidney vessels showed ischemia of kidney parenchyma which is caused by a disruption of arterial blood flow, which is typical of the prerenal form of acute renal insufficiency. As a result, filtration in the kidneys was reduced and azotemia arose. The treatment was aimed at restoring homeostasis and eliminating the cause. For this purpose, we applied infusion therapy, correction of electrolyte imbalance, etiotropic treatment, diuretics for restoration of diuresis when needed. Thus, the diagnosis of acute renal failure in dogs should be comprehensive and based on disease history, clinical examination, blood and urine test analysis, additional research methods (visual diagnostic). Treatment should be aimed at restoring homeostasis and eliminating the cause with the introduction of infusion therapy, correction of electrolyte imbalance, etiotropic therapy, and the use of diuretics if necessary.
Diagnosis and treatment characteristics of acute renal failure in dogs
https://orcid.org/0000-0001-9500-9224
Keywords: креатинін; creatinine; хвороби нирок; kidney disease; ультразвукове дослідження; ultrasound; доплерографія; dopplerography; сечовина; urea